PENGARUH LAMA USAHA, MODAL, JENIS BARANG JUALAN DAN UMUR TERHADAP PENDAPATAN PEDAGANG DIPASAR AURDURI - Nabela Alfatia; Zamzami; Sri Ningsih (Jurnal Riset Multidisiplin Edukasi, 2026)
This research analyzes the influence of business duration, working capital, type of goods sold, and trader age on traders' income at Aurduri Market. A quantitative approach using multiple linear regression analysis through SPSS 30 and eview 30 was applied to primary data from 60 market traders. The F-test results indicate that all four variables simultaneously and significantly affect income (F-statistic = 285.8498; Prob(F-statistic) = 0.000 < 0.05). Individually, each variable also shows positive and significant effects (p < 0.05), suggesting that increases in business duration, capital amount, suitability of goods sold, and trader age lead to higher income. The coefficient of determination R² = 0.954 (95.41%) demonstrates that the model explains most income variation, with 4.59% influenced by other factors. Validity testing via Corrected Item-Total Correlation confirms all indicators are valid (range 0.977–0.985 > 0.30), while reliability testing yields Cronbach's Alpha = 0.992 (> 0.90), indicating highly reliable instruments. These findings offer practical contributions for traditional market managers to enhance trader welfare through optimized working capital, strategic commodity selection, business experience development, and empowerment of productive-age traders. The study also enriches microeconomic literature on income determinants for traditional market traders in Indonesia.